Uncertainty of measurement: an immunology laboratory perspective. (January 2015) - Beck, Sarah C; Lock, Robert J
'Measurement uncertainty of measured quantity values' (ISO15189) requires that the laboratory shall determine the measurement uncertainty for procedures used to report measured quantity values on patients' samples. Where we have numeric data measurement uncertainty can be expressed as the standard deviation or as the co-efficient of variation. However, in immunology many of the assays are reported either as semi-quantitative (i.e. an antibody titre) or qualitative (positive or negative) results. In the latter context, measuring uncertainty is considerably more difficult. There are, however, strategies which can allow us to minimise uncertainty. A number of parameters can contribute to making measurements uncertain. These include bias, precision, standard uncertainty (expressed as standard deviation or coefficient of variation), sensitivity, specificity, repeatability, reproducibility and verification. Closely linked to these are traceability and standardisation. In this article we explore the challenges presented to immunology with regard to measurement uncertainty. Many of these challenges apply equally to other disciplines working with qualitative or semi-quantitative data.